The Effect of Applying K-W-L Technique on Teaching ESP Students (Journal Of Educational and Psychological Researches, 2010)
Over the last few decades, many instructors have been trying all kinds of teaching methods, but without benefit. Nevertheless, in the 1986, a new technique is appeared which called K-W-L technique, it  is specified for reading comprehension passages because reading  skill is not easy matter for students for specific purposes (ESP).therefore, the K-W-L technique is a good one for thinking and experiences. To fulfill the aims and verify the hypothesis which reads as follows" it is hypothesized that there are no significant differences between the achievements of students who are taught according to K-W-L technique and those who are taught according to the traditional method.            T- test for two independent samples is used to analyse the final test. The analysis of results shows that experimental group who are taught according to K-W-L technique is better than control group who are taught according to lecture method. Finally, the outcomes of present research appeared that K-W-L enables the students to activate their prior knowledge and operate their thinking, besides the students centered the classroom activity and they learn what they want to learn and interest.